Comprehensive Analysis of a Ferroptosis-Related lncRNA Signature for Predicting Prognosis and Immune Landscape in Osteosarcoma - Zhang, Yiming; He, Rong; Lei, Xuan; Mao, Lianghao; Yin, Zhengyu; Zhong, Xinyu; Cao, Wenbing; Zheng, Qiping; Li, Dapeng (Frontiers in Oncology, 2022)
Osteosarcoma is the most common primary malignant bone tumor associated with frequent recurrence and lung metastasis. Therefore, early biomarkers and therapeutic targets are urgently needed. Ferroptosis and long non-coding RNAs (lncRNAs) play a critical role in regulating several aspects of cancer biology, including tumor progression, metastasis, immunomodulation, and therapeutic response. Nonetheless, the interaction between ferroptosis-related lncRNAs (FRLs) and the osteosarcoma immune microenvironment is poorly understood. In this study, we investigated whether FRLs could predict prognosis and immune characteristics in osteosarcoma patients. We screened for 43 prognosis-related FRLs and identified two molecular subtypes with different clinical outcomes by consensus clustering analysis. Subsequently, we constructed an FRL prognostic signature for osteosarcoma called "FRL-score" using LASSO Cox regression analysis. Single-sample Gene Set Enrichment Analysis (ssGSEA) and ESTIMATE analysis demonstrated that the FRL-score could distinguish immune function, immune score, stromal score, tumor purity, and tumor infiltration of immune cells in different osteosarcoma patients. Independent prognostic analysis showed FRL-score was an independent prognostic factor in osteosarcoma compared to traditional clinical characteristics. In addition, FRL-score was also associated with immune checkpoint gene expression and half-maximal inhibitory concentration of chemotherapeutic agents. Finally, we confirmed that knockdown of RPARP-AS1 suppressed the malignant activity of osteosarcoma cells in vitro experiments. In conclusion, we evaluated the prognostic value and clinical application of an FRL-based prognostic signature and identified promising biomarkers for predicting immune microenvironment and immunotherapy response in osteosarcoma.